What does the brain of children with developmental dyslexia tell us about reading improvement? ERP evidence from an intervention study - Hasko, Sandra; Groth, Katarina; Bruder, Jennifer; Bartling, Jürgen; Schulte-Körne, Gerd (Frontiers in Human Neuroscience, 2014)
Intervention is key to managing developmental dyslexia (DD), but not all children with DD benefit from treatment. Some children improve (improvers, IMP), whereas others do not improve (non-improvers, NIMP). Neurobiological differences between IMP and NIMP have been suggested, but studies comparing IMP and NIMP in childhood are missing. The present study examined whether ERP patterns change with treatment and differ between IMP and NIMP. We investigated the ERPs of 28 children with DD and 25 control children (CON) while performing a phonological lexical decision (PLD) task before and after a 6-month intervention. After intervention children with DD were divided into IMP (n=11) and NIMP (n=17). In the PLD–task children were visually presented with words, pseudohomophones, pseudowords and false fonts and had to decide whether the presented stimulus sounded like an existing German word or not. Prior to intervention IMP showed higher N300 amplitudes over fronto-temporal electrodes compared to NIMP and CON and N400 amplitudes were attenuated in both IMP and NIMP compared to CON. After intervention N300 amplitudes of IMP were comparable to those of CON and NIMP. This suggests that the N300, which has been related to phonological access of orthographic stimuli and integration of orthographic and phonological representations, might index a compensatory mechanism or precursor that facilitates reading improvement. The N400, which is thought to reflect grapheme-phoneme conversion or the access to the orthographic lexicon increased in IMP from pre to post and was comparable to CON after intervention. Correlations between N300 amplitudes pre, growth in reading ability and N400 amplitudes post indicated that higher N300 amplitudes might be important for reading improvement and increase in N400 amplitudes. The results suggest that children with DD, showing the same cognitive profile might differ regarding their neuronal profile which could further influence reading improvement.